Active-site engineering in dealloyed nanoporous catalysts for electrocatalytic water splitting. Issue 2 (14th December 2022) - Qiao, Yijin; Peng, Ming; Lan, Jiao; Jiang, Kang; Chen, Dechao; Tan, Yongwen
Abstract : In this review, we comprehensively discuss the unique advantages, the recent advances and the future development prospects in dealloyed nanoporous materials for electrocatalytic water splitting from the perspective of active-site engineering. Abstract : Electrochemical water splitting to produce hydrogen as an ideal sustainable energy storage strategy provides a useful approach for the utilization of clean energy due to its high theoretical energy conversion efficiency, simplicity of the device and environmental friendliness. However, there remains a crying need to develop advanced electrocatalysts that can satisfy anticipatory standards, such as pH-universal catalytic capability, superior catalytic activity, robust long-term durability, and low cost. Dealloyed nanoporous electrocatalysts with unique mass and electron transport characteristics, large specific surface area, high intrinsic catalytic activity, as well as excellent synergistic ability of active sites, have attracted extensive attention in the field of electrocatalytic water splitting. In this review, we thoroughly elaborate on active-site engineering of dealloyed nanoporous electrocatalysts with an emphasis on the design strategy of active sites. Subsequently, the recent progress of promising dealloyed nanoporous electrocatalysts for electrocatalytic water splitting is introduced. Finally, a brief summary is given and the bottlenecks relating to promotion of dealloyed nanoporous electrocatalysts for sustainable large-scale water splitting are put forward along with future development prospects.